Broad HIV epitope specificity and viral inhibition induced by multigenic HIV-1 adenovirus subtype 35 vector vaccine in healthy uninfected adults. - Jakub Kopycinski; Peter Hayes; Ambreen Ashraf; Hannah Cheeseman; Francesco Lala; Justyna Czyzewska-Khan; Aggeliki Spentzou; Dilbinder K Gill; Michael C Keefer; Jean-Louis Excler; Patricia Fast; Josephine Cox; et al. (PLoS ONE, 2014)
A correlation between in vivo and in vitro virus control mediated by CD8+ T-cell populations has been demonstrated by CD8 T-cell-mediated inhibition of HIV-1 and SIV replication in vitro in peripheral blood mononuclear cells (PBMCs) from infected humans and non-human primates (NHPs), respectively. Here, the breadth and specificity of T-cell responses induced following vaccination with replication-defective adenovirus serotype 35 (Ad35) vectors containing a fusion protein of Gag, reverse transcriptase (RT), Integrase (Int) and Nef (Ad35-GRIN) and Env (Ad35-ENV), derived from HIV-1 subtype A isolates, was assessed in 25 individuals. The vaccine induced responses to a median of 4 epitopes per vaccinee. We correlated the CD8 responses to conserved vs. variable regions with the ability to inhibit a panel of 7 HIV-1 isolates representing multiple clades in a virus inhibition assay (VIA). The results indicate that targeting immunodominant responses to highly conserved regions of the HIV-1 proteome may result in an increased ability to inhibit multiple clades of HIV-1 in vitro. The data further validate the use of the VIA to screen and select future HIV vaccine candidates. Moreover, our data suggest that future T cell-focused vaccine design should aim to induce immunodominant responses to highly conserved regions of the virus.